Treatment with Soteria-elements in acute psychiatry—Effectiveness for acutely ill and voluntarily treated patients - Fabel, Philine; Wolf, Theresa; Zyber, Helena; Rubel, Julian; Jockers-Scherübl, Maria C. (Frontiers in Public Health, 2023)
Objective This article aims at evaluating the treatment outcomes of acute psychiatric patients before and after the implementation of Soteria-elements in an acute psychiatric ward. The implementation process resulted in an interconnected small locked and much larger open area, enabling continuous milieu therapeutic treatment by the same staff in both areas. This approach enabled the comparison of structural and conceptual reconstruction regarding treatment outcomes of all voluntarily treated acutely ill patients before (2016) and after (2019). A subgroup analysis focused on patients suffering from schizophrenia. Methods Using a pre-post design, the following parameters were examined: total treatment time, time in locked ward, time in open ward, antipsychotic discharge medication, re-admissions, discharge circumstances, and treatment continuation in day care clinic. Results Compared to 2016, there was no significant difference in the total time of stay in the hospital. However, data show a significant decrease of days spent in locked ward, a significant increase of days in open ward, a significant increase of treatment discontinuation but without an increase of re-admissions, and a significant interaction of diagnosis and year regarding the medication dosage, resulting altogether in a reduction of antipsychotic medication for patients suffering from schizophrenia spectrum disorder. Conclusion The implementation of Soteria-elements in an acute ward facilitates less potentially harmful treatments of psychotic patients, likewise enabling lower dosages of medication.